Maternal Self-Report of Oral Health in 4-Year-Old Pacific Children from South Auckland, New Zealand: Findings from the Pacific Islands Families Study - Philip J. Schluter, PhD; Callum Durward, BDS, MDSc, MPH; Susan Cartwright, (Blackwell Synergy, 2007)
To report on the oral health risk in a disadvantaged group of 4-yearold Pacific children and their mothers living in South Auckland, New Zealand.